Encyclopaedia of physical education and sports Vol.6 Major issues in the administration of physical education - Mudgal, Rahul (Ed); Kaushik, Vijaya (ed); Kaushik, Vijaya (Ed.) (New Delhi Sarup Book Publishers, 2012)
Physical education plant